2014
DOI: 10.1007/s11010-014-2057-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of pathogenic beta1-receptor autoantibodies by aptamers in vivo: the first successful proof of principle in spontaneously hypertensive rats

Abstract: Autoantibodies (AABs) against the second extracellular loop of the beta1-receptor (beta1(II)-AABs) are found as a pathogenic driver in patients with idiopathic dilated cardiomyopathy, Chagas cardiomyopathy, peripartum cardiomyopathy, and myocarditis, and have been increasingly seen as a treatment target. We recently identified an aptamer (single short DNA strand) that specifically binds and neutralizes beta1(II)-AABs. Via application of this aptamer, a new treatment strategy for diseases associated with the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…This peptide acts comparable to the second loop mimics COR-1 which was already studied to counteract β1-AAB in patients with DCM (14). The other two substances are aptamers (15,35): the first (aptamer 110; D2) is able to neutralize only β1-AAB due to specific β1-AAB binding, which was demonstrated in vitro and in an animal study (36,37), while the second (BC 007; D3), as demonstrated in animal and human studies, is able to inhibit several GPCR-AAB, including β1-AAB and M2-AAB (38,39). After drug pre-incubation of β1-AAB or M2AAB containing IgG from DP with the drugs (test concentration 1 μmol/l), the mixture was added to the bioassay for measurement of the chronotropic activity of IgG.…”
Section: Methodsmentioning
confidence: 99%
“…This peptide acts comparable to the second loop mimics COR-1 which was already studied to counteract β1-AAB in patients with DCM (14). The other two substances are aptamers (15,35): the first (aptamer 110; D2) is able to neutralize only β1-AAB due to specific β1-AAB binding, which was demonstrated in vitro and in an animal study (36,37), while the second (BC 007; D3), as demonstrated in animal and human studies, is able to inhibit several GPCR-AAB, including β1-AAB and M2-AAB (38,39). After drug pre-incubation of β1-AAB or M2AAB containing IgG from DP with the drugs (test concentration 1 μmol/l), the mixture was added to the bioassay for measurement of the chronotropic activity of IgG.…”
Section: Methodsmentioning
confidence: 99%
“…3) Over the past decade, aptamers have been used in several experimental cardiovascular applications, including amelioration of cardiotoxicity, biomarker discovery, and improvement of cardiac muscle contractility [160][161][162] . Other examples include osteopontin RNA aptamers that reduced cardiac hypertrophy and fibrosis in a mouse model of heart failure induced by pressure overload 163 and aptamers designed to neutralize G-coupled receptor autoantibodies for potential treatment of cardiomyopathies 164 or to neutralize β1-adrenergic receptor autoantibodies as a potential therapeutic strategy in hypertension 165 . Clinical challenges of aptamers-based strategies to be addressed include duration of action and rapid degradation rates, excretion by renal filtration, interaction with nonspecific targets, and automation for mass production 159 .…”
Section: [H1] Clinical Prospectsmentioning
confidence: 99%
“…In einem zweiten Konzept werden Aptamere zur in vivo Neutralisation von GPCR-AAK eingesetzt. Für ein spezifisch beta1-AAK bindendes Aptamer als auch für ein Aptamer, das alle in Tabelle 1 aufgeführten GPCR-AAK bindet, wurde die neutralisierende Wirkung auf die jeweiligen GPCR-AAK im Zellsystem und im Tierversuch nachgewiesen [15][16][17]. Verglichen mit Peptiden oder Aptameren mit Spezifität für jeweils nur einen GPCR-AAK könnte das Aptamer, das parallel verschiedenste GPCR-AAK neutralisiert, ein deutlich umfangreicheres Indikationsgebiet finden, insbesondere auch für Patienten von Vorteil sein, deren Erkrankung von mehreren GPCR-AAK determiniert ist (z.B.…”
Section: Vo Nikolaev (Göttingen) "Analytik Von Autoantikörpern Gegeunclassified